Luna's moustache - Ocampo, Ambeth R., 1961-; Vicente L. Rafael (Pasig City : Anvil Pub, 1997)
Articles from the author's column in the Philippines Daily Inquirer
Keywords: Philippines -- History -- Anecdotes; Philippines -- History -- Errors, inventions, etc